A study of heavy rainfall occurrence at Santacruz (Bombay) with special reference to supersonic flight operations (MAUSAM, 1969)
Heavy rain is one of the meteorological phenomena that poses a problem for the operation of supersonic transport aircraft in subsonic phases of climb and descent. Raindrops in high concentrations and sizes associated with heavy rain effect damage on impact on the forward facing parts of the aircraft moving at high speeds even in, the subsonic range. Santacruz (Bombay) experiences heavy rainfall spells during the southwest. Monsoon period. The frequency of these spells and an analysis of the hyetograms for the period 1954-64 have been carried out. Graphs showing the average hourly rainfall and the diurnal variation on occasions of heavy rain spells are presented. The frequency of spells of heavy rain at two sites when there is a large variation of rainfall or otherwise have been studied with special reference to the upper winds on these situations. It is seen that whenever there is a large variation of rainfall at the two sites, the prevailing westerlies are strong and extend to a deeper layer upto 3 km or more.